The Influence of Service Quality on Customer Satisfaction: A Case Study - Syahsudarmi, Siti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
The purpose of this study was to determine whether service quality has an effect on customer satisfaction. With a case study on a snack food supplier company. the population of this study is all suppliers who shop at PT. Sinar Niaga Sejahtera Duri-Riau, totaling 1,080 people, using the slovin formula, obtained 95 samples as respondents in this study. For hypothesis testing and data processing, SPSS version 24 was used. It was found from the determination test that the value of R square was 0.509, which means that service quality affects customer satisfaction, the value is 50.9% while the remaining 49.1% is influenced by other independent variables. not observed in this study.